Bagdat Street in the Grip of Urban Transformation - Berkmen, Naime Hulya; Turgut, Sirma (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
In this study, urban transformation and the process of spatial change that have been taking place in different settlement places in Bagdat Avenue, which is a research subregion with diverse dynamics in terms of urban transformation practices that occur throughout country since 2012, is discussed. The aim of the study is to elaborate this transformation process and its results, which takes place in one of the oldest prestige settlements of Istanbul, Bagdat Avenue, and in its surroundings, based on the approaches and expectations of settlement users, sector representatives, local and central authority actors, and especially the property owners; and to detect and evaluate the impact of the transformation applications on the general structure of the region. Similar to the other parts of the country, Kadikoy has also entered the urban transformation process, which is utilized as the most popular tool for the spatial reproduction. Urban transformation process, which especially gained momentum with Law no. 6306 on the Transformation of Areas at Risk of Natural Disaster that entered into force in 31.05.2012 (R. G. 28309), has become an important triggering factor for the settlement areas near Bagdat Avenue. The findings of the study are evaluated specifically in two examplary subregions. Consisting of a wideness of 15.000 m(2), one of these subregions is the settlement area in Erenkoy District, in the North of Bagdat Avenue, in between the Avenue and Railway Road; whereas the other one is situated in the South of the Avenue, in Fenerbahce District, in between Bagdat Avenue and KadikoyBostanci coastal road (Kalamis Street). The aforementioned subregions are elaborated and evaluated in frames of the urban transformation process, and in terms of spatial reorganization. This change and transformation that occur specifically in these settlements are discussed in the context of physical space, economical structure and their user profiles.
Keywords: Bagdat Street; Kadikoy; urban transformation; Architecture